The Effect of Genre-Based Approach on Students' Proficiency in Writing Recount Text at Islamic Boarding Schools - Dian Kusuma; Setia Rini (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper investigates the effectiveness of teaching recount texts using a genre-based approach on Islamic boarding school students. The research adopts a quantitative approach with a pre-experimental method, specifically the One-Group Pre-test-Post-test Design. The sample consists of 10 students from Class VIII of MTs SA Miftahul Huda Pabelan, which was selected based on specific criteria. The data were analyzed using the Paired Sample Test, which resulted in a significance value (Sig.) of 0.000. Based on the predetermined criteria, a significance value below 0.05 leads to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (Ha). In addition, there is a significant difference in the average scores between the Pre-test and Post-test, which were a pre-test mean score of 58.6 and a post-test mean score of 68.6. These findings indicate the effectiveness of the genre-based approach in improving students' skills to write recount texts in the boarding school context. In conclusion, the genre-based approach is effective in enhancing students' writing skills in the recount texts in the boarding school based on the findings.